2010
DOI: 10.1007/s11661-010-0576-9
|View full text |Cite
|
Sign up to set email alerts
|

Macrosegregation of Impurities in Directionally Solidified Silicon

Abstract: Directional solidification of molten metallurgical-grade Si was carried out in a vertical Bridgman furnace. The effects of changing the mold velocity from 5 to 110 lm seconds -1 on the macrosegregation of impurities during solidification were investigated. The macrostructures of the cylindrical Si ingots obtained in the experiments consist mostly of columnar grains parallel to the ingot axis. Because neither cells nor dendrites can be observed on ingot samples, the absence of precipitated particles and the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 53 publications
2
10
0
7
Order By: Relevance
“…Therefore, the accumulation of SiC particles at the ingot top can only have occurred during the solidification experiments. For the lowest mold velocities, namely 5, 10, and 20 lm/s, a planar solid-liquid interface is expected, as described by Martorano et al [12,13] The structure of columnar grains aligned in the axial direction observed for these velocities (Figures 3(a) through (c)) is consistent with a planar solid-liquid interface growing upward, pushing the SiC particles to the ingot top and causing the larger carbon concentration in this region (Figure 1). An accumulation of precipitated particles was confirmed at the ingot top for these experiments, as seen in Figures 5(b) and (d).…”
Section: Effects Of Mold Pulling Velocity On Carbon Macrosegregationmentioning
confidence: 53%
See 1 more Smart Citation
“…Therefore, the accumulation of SiC particles at the ingot top can only have occurred during the solidification experiments. For the lowest mold velocities, namely 5, 10, and 20 lm/s, a planar solid-liquid interface is expected, as described by Martorano et al [12,13] The structure of columnar grains aligned in the axial direction observed for these velocities (Figures 3(a) through (c)) is consistent with a planar solid-liquid interface growing upward, pushing the SiC particles to the ingot top and causing the larger carbon concentration in this region (Figure 1). An accumulation of precipitated particles was confirmed at the ingot top for these experiments, as seen in Figures 5(b) and (d).…”
Section: Effects Of Mold Pulling Velocity On Carbon Macrosegregationmentioning
confidence: 53%
“…To derive the Scheil equation, the solute transport in the liquid is assumed sufficiently rapid to homogenize its composition. When a more slowly mass transport is assumed, the concentrations at lower relative distances (h/H) would increase and also shift the profile upward, [12] increasing the discrepancy. Therefore, it seems possible to conclude that the measured concentration profiles were not caused by simple carbon rejection by the solid into the liquid at a planar solidliquid interface during the upward solidification.…”
Section: Effects Of Mold Pulling Velocity On Carbon Macrosegregationmentioning
confidence: 99%
“…A formação da macrossegregação na solidificação dendrítica é geralmente atribuída ao transporte convectivo de soluto no líquido ou à movimentação do sólido [1], mas, durante a solidificação direcional com interface sólido-líquido planar, a macrossegregação pode se formar apenas com o transporte difusivo de soluto [2][3][4]. Modelos matemáticos já foram propostos para descrever a macrossegregação induzida pelo transporte difusivo de soluto na interface sólido-líquido planar [5,6,3], nos quais a interface é assumida plana mesmo em condições de solidificação que resultariam em uma zona pastosa com células ou dendritas, o que poderia modificar completamente o perfil de macrossegregação observado [7]. Caso seja assumida a existência de uma zona pastosa, um conjunto diferente de equações é adotado para a solidificação direcional de ligas [8][9][10][11].…”
Section: Introductionunclassified
“…No entanto, nestes casos a macrossegregação formada apenas pela difusão de soluto ainda não foi analisada, sendo que ela se torna importante quando a solidificação direcional é conduzida em condições de baixas velocidades de solidificação e altos gradientes térmicos, que podem originar interfaces sólido-líquido celulares. Um exemplo de tal processo é a purificação de silício para células solares [3]. Análises anteriores obtidas na literatura demonstram que, para o modelamento da solidificação direcional e da macrossegregação resultante quando a interface plana desestabiliza em uma zona pastosa, são necessários três conjuntos de equações para (1) prever a existência de uma zona pastosa ou de uma interface plana, (2) modelar o transporte de soluto no líquido, e (3) modelar o transporte de soluto na zona pastosa.…”
Section: Introductionunclassified
“…The purification of MG-Si through metallurgical routes such as directional solidification [1,2], slag refining [3][4][5], oxidation with plasma melting [6][7][8][9], and vacuum melting [10,11] has been investigated. The individual process has its own limitations and does not allow removal of all impurities.…”
Section: Introductionmentioning
confidence: 99%